Nuclear Power: Black Sky Liability or Black Sky Asset? - Sherrell R. Greene (International Journal of Nuclear Security, 2016)
Ready access to abundant electricity is a key enabler of modern life. During the past decade the vulnerability of Critical Infrastructure sectors in the U.S. to a variety of natural hazards and man-made threats has become increasingly apparent. The electrical infrastructure (the “Grid”) is the foundation for all other critical civil infrastructures upon which our society depends. Therefore, protection of the Grid is an energy security, homeland security, and national security issue of highest importance. Geomagnetic disturbances (GMD) induced by solar coronal mass ejections (CMEs), electromagnetic pulse (EMP) attacks, and cyber attacks are three events having the potential to plunge the U.S. into partial or total Grid failure (de-energization) with subsequent blackouts so massive they are referred to as “Black Sky Events”. Embedded in the U.S. Grid are almost one hundred commercial nuclear power reactors in some sixty nuclear power plants (NPPs). This paper explores the nature of society’s coupled “system of systems” (i.e. Grid, other Critical Infrastructure, human operators of these infrastructures, Government, and the Public) that would be stressed by a Black Sky Event, and presents an analytical framework for probing the behavior of this system during Black Sky Events. The question of how NPPs might be impacted by a prolonged Black Sky Event, and what role, if any, NPPs can play in enabling a rapid recovery from a Black Sky Event is examined. The likely behavior of an NPP during a Black Sky Event is discussed, and it is concluded that today’s generation of NPPs are Black Sky liabilities. However, a unique characteristic of NPPs (the large fuel inventory maintained in the reactor) could make the NPPs extraordinarily valuable assets should a Black Sky Event occur. Their value in this regard depends on whether or not it might be possible to affect a number of changes in the NPPs, the U.S. Grid, and other Critical Infrastructure in the U.S. to enable the NPPs to become Black Start Units – generating stations that would be the foundation of recovering the U.S. Grid during a Black Sky Event. This paper poses the question, “Can today’s nuclear power plants be transformed from Black Sky Liabilities to Black Sky Assets, and if so, how?” An integrated framework for addressing this question is proposed.
Keywords: Nuclear Power; Black Sky; Energy Security; Critical Infrastructure; Electricity; Grid; GMD; CME; EMP